Infection of reproductive system of buffaloes and cattle with Pasteurella multocida: a review of pathophysiological alterations - Ibrahim, Hayder Hamzah; Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Marza, Ali Dhiaa; Saad, Mohd Zamri; Haron, Abd Wahid; Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2016)
Serotypes B: 2 and E: 2 of Haemorrhagic septicaemia found in Asia and Africa cause an economically important disease that affects cattle and buffaloes. The disease has a feature of short clinical course and high morbidity and mortality rates. However, animals surviving HS are usually characterized by decrease productivity. There is paucity of knowledge in the involvement of the reproductive system and its organizer hormones in animals afflicted with HS. Therefore, this review aimed to gather information and provide more details on reproductive pathophysiology and its modifications in buffaloes and cattle as a result of P. multocida B: infections.